A Southern Music: The Karnatik Story - T.M Krishna (Harpercollins Publishers India, 2015)
One of the foremost Karnatik vocalists today, T.M. Krishna writes lucidly and passionately about the form, its history, its problems and where it stands todayT.M. Krishna begins his sweeping exploration of the tradition of Karnatik music with a fundamental question: what is music? Taking nothing for granted and addressing readers from across the spectrum-musicians, musicologists as well as laypeople-Krishna provides a path-breaking overview of south Indian classical music.